2014
DOI: 10.1037/a0031992
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation power of extrinsic rewards: Reward cues enhance long-term memory for irrelevant past events.

Abstract: Recent research suggests that extrinsic rewards promote memory consolidation through dopaminergic modulation processes. However, no conclusive behavioral evidence exists given that the influence of extrinsic reward on attention and motivation during encoding and consolidation processes are inherently confounded. The present study provides behavioral evidence that extrinsic rewards (i.e., monetary incentives) enhance human memory consolidation independently of attention and motivation. Participants saw neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
116
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 46 publications
17
116
0
1
Order By: Relevance
“…While the latter could result from a preferential allocation of study time (Castel et al ., 2002) to HL versus nHL content, our results are consistent with an account of dopaminergic modulation of hippocampal‐based consolidation, with dopamine likely affecting hippocampal plasticity and memory during the hours after encoding (Shohamy and Adcock, 2010), and especially during sleep (Perogamvros and Schwartz, 2012). This could explain why previous studies have found that reward cues led to increased memory following 24‐h (Spaniol et al ., 2013) and 1‐week (Murayama and Kitagami, 2014) delays, but not immediately.…”
Section: Discussionmentioning
confidence: 99%
“…While the latter could result from a preferential allocation of study time (Castel et al ., 2002) to HL versus nHL content, our results are consistent with an account of dopaminergic modulation of hippocampal‐based consolidation, with dopamine likely affecting hippocampal plasticity and memory during the hours after encoding (Shohamy and Adcock, 2010), and especially during sleep (Perogamvros and Schwartz, 2012). This could explain why previous studies have found that reward cues led to increased memory following 24‐h (Spaniol et al ., 2013) and 1‐week (Murayama and Kitagami, 2014) delays, but not immediately.…”
Section: Discussionmentioning
confidence: 99%
“…The status of reward (versus no reward) as one factor in promoting memory in both incidental and motivated learning has been established across a number of studies (Adcock, Thangavel, WhitfieldGabrieli, Knutson, & Gabrieli, 2006;Murayama & Kitagami, 2014;Wittmann, Dolan, & Düzel, 2011;Wittmann et al, 2005). However, the degree to which small variations in reward can influence memory is still unclear.…”
mentioning
confidence: 99%
“…Emotion is often studied using stimuli that are inherently emotional-words, pictures, sounds, or videos that themselves semantically connote emotional content (Kensinger et al, 2007;MacKay et al, 2004;Madan et al, , 2017cShafer et al, 2012;Shigemune et al, 2010;Strange et al, 2003). In contrast, reward is often implemented as an instructional cue or feedback outcome (Adcock et al, 2006;Castel et al, 2002;Mason et al, 2017;Murayama & Kitagami, 2014;Murty et al, 2012;Pessiglione et al, 2007;Shigemune et al, 2010;Shohamy & Adcock, 2010;Spaniol et al, 2013). Though this dissociation is often true, there are exceptions-such as emotion studies where emotionally neutral stimuli are associated with emotional responses through a similar training task (Mather & Knight, 2008), emotional stimuli are presented just prior to the stimuli of interest (Qiao-Tasserit et al, 2017;Xie & Zhang, 2016, or with emotional stimuli are used as a feedback signal (Finn & Roediger, 2011).…”
mentioning
confidence: 99%